PENERAPAN METODE TALAQQI DALAM MEMBACA Al-QUR’AN DI PONDOK PESANTREN IBNU KASIM NAHDLATUL WATHAN BINTAN - Nazaruddin; Ahmad Fadhil Rizki; Milasari; Marlin (Miftahul Ulum, 2023)
This study aims (1) to determine the application of the talaqqi method at the Islamic Boarding School of Ibnu Kasim Nahdlatul Wathan Bintan. (2) To determine the ability of students to read the Qur'an at the Pondok Pesantren Ibnu Kasim Nahdlatul Wathan Bintan. (3) To determine the effect of the application of the talaqqi method on the ability of students to read the Qur'an at the Pondok Pesantren Ibnu Kasim Nahdlatul Wathan Bintan. The research subjects were all 83 students at the Ibnu Kasim Nahdlatun Islamic Boarding School, Wathan Bintan. Data collection techniques using observation, interviews, questionnaires, tests and documentation to students.The results of this study indicate that the talaqqi method reaches 67.2%. This is evident from the results of the questionnaire which reached 67.2% which was in the range of 61% -80% in the Good category. While the results of the research on the ability of students to read the Qur'an, reached 63.2%. This is evident from the results of the questionnaire data which reached 63.2% which was in the range of 61% -80% in the Good category.The Influence of the Application of the Talaqqi Method on the Ability of Students in Reading the Qur'an at the Islamic Boarding School of Ibnu Kasim Nahdlatun Wathan Bintan, the calculation results obtained that the value of rxy = 0.977 was between the values (0.90 - 1.00). Thus, rcount is greater than rtable at a significance level of 5% and a significance level of 1% (181>215>0.977), which means that Ha is accepted and Ho is rejected. So the value of the correlation analysis shows that there is an effect of the application of the Talaqqi method on the ability of students to read the Qur'an at the Pondok Pesantren Ibnu Kasim Nahdlatun Wathan Bintan of 95.4%.